Pengembangan Sistem Pemetaan Sebaran UMKM Menggunakan WEBGIS (Studi Kasus: Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo) - Johan Nur Rokhman; Faizatul Amalia; Fatwa Ramdani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
UMKM are the driving force of the regional economy. The Office of Cooperatives and Micro Enterprises has an important role in the development of UMKM. The very fast growth of UMKM in Sidoarjo Regency causes a lack of information on UMKM in Sidoarjo Regency. Problems that are often faced are related to MSME data collection which is still not optimal, data collection is still using a questionnaire then the data is recapitulated by administrative officers using Microsoft Excel so that it requires a lot of time and human resources and people who need information about UMKM must come directly to the Cooperative and Micro Business Office. With this website, it is hoped that it will make it easier for service employees to collect data and make it easier for the public to get information on UMKM and to be able to access MSME locations by utilizing the WebGis available in the system. This study uses the Waterfall method. Elicitation is carried out by interviewing employees of the Cooperative and Micro Business Office. There were 20 functional systems implemented with the PHP programming language and the map library used, namely Leaflet Js. The results of this study were a map display along with information on the distribution of UMKM. Black box testing is used the UAT method and for the white box using flowgraph. And for usability testing, the SUS method was used, the results were 77%, which means good. To test the accuracy, the test matrix table is used, the results are 85%.